Social Care Based on Local Wisdom for People with Disabilities in Bongki Village, Sinjai Regency - Rahman, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine local wisdom-based community concern for people with disabilities. This research uses qualitative research. Data was obtained by field research using observation, interviews and documentation methods, involving the community and government officials. The results of this research show that in society's view of people with disabilities, no human being is born perfect, because Allah SWT created humans each equipped with their own strengths and weaknesses. Likewise with people who have physical limitations, people with disabilities are stated in the cultural norms and values ​​of sipakatau, sipakainge and sipakalebbi (3S). The community in Bongki Village, North Sinjai District, Sinjai Regency always provides support to people with disabilities. One way of showing this support is social support as the presence of people who personally provide advice, motivate, direct, encourage and show a way out when experiencing problems and when experiencing obstacles in carrying out activities in a directed manner to achieve goals